2006
DOI: 10.1590/s0004-27302006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome da apnéia e hipopnéia obstrutiva do sono: associação com obesidade, gênero e idade

Abstract: Obstructive sleep apnea and hypopnea syndrome (OSAHS) has been the focus of extensive research because of its association with neurocognitive and cardiovascular complications. The aim of this study was to evaluate the frequency and association between OSAHS and the class of obesity, gender and age in outpatients referred to a sleep laboratory. We selected 1,595 patients, 71.7% male. Mean +/- SD age was 46.7 +/- 11.7 years, BMI was 28.1 +/- 5.1 kg/m2 and AIH was 13.9 +/- 15.5 events/ hour of sleep. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
(47 reference statements)
2
9
0
16
Order By: Relevance
“…Furthermore, the obstructive sleep apnea and hypopnea syndrome, a fairly common sleep disorder among obese individuals, is more prevalent and serious among menopausal women (19) , and 21 women in the present study are in this stage in life (56.76%).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, the obstructive sleep apnea and hypopnea syndrome, a fairly common sleep disorder among obese individuals, is more prevalent and serious among menopausal women (19) , and 21 women in the present study are in this stage in life (56.76%).…”
Section: Discussionmentioning
confidence: 53%
“…This can occur due to the distribution of fat in males, which implies an accumulation of fat tissue in the upper part of their body, thus favoring a greater collapse of the upper airways in males. [20][21][22][23] After evaluating Category 1 in the BQ, we found that 70% of the sample scored positively, which demonstrates that these individuals have snoring symptoms and witnessed apneas. Snoring and sleep apnea are both the progression of a single problem to OSAS.…”
Section: Discussionmentioning
confidence: 81%
“…As consequências do ronco e SAOS são: acordar cansado, geralmente com cefaléia e mau humor, hipersonolência diurna, hipoventilação pulmonar e consequente redução de oxigenação do sangue ou hipóxia, durante os períodos de apneia, terminam por produzir hipertensão pulmonar, que acarreta sobrecarga cardíaca e hipertensão arterial, além de roncos altos, engasgos, pausas respiratórias, sono agitado, múltiplos despertares, boca seca, sudorese, necessidade de urinar várias vezes à noite, queda no rendimento intelectual, impotência sexual, dé cit de atenção, concentração e memória, de ciências neurocognitivas, alterações na personalidade, impacto social, pois a sonolên-cia excessiva pode causar problemas pro ssionais, assim como, acidentes automobilísticos e os roncos altos, causam desajustes conjugais 3,6,24,35 . Devido a esses fatores, esta síndrome é atualmente considerada um problema de saúde pública por causar aumento de acidentes de trânsito e trabalho, bem como, da morbi-mortalidade cardiovascular 18,19,36 .…”
Section: Manifestaçõesunclassified